Precarious perinatal care: experiences of incarcerated individuals in Ontario, Canada - Bancroft, Xaand; McGee, Amy; Ferron Parayre, Audrey; Morgan, Lisa; Peterson, Wendy E. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Incarcerated pregnant individuals face substantial barriers to timely and appropriate perinatal care, which may contribute to poorer maternal and newborn health outcomes compared to the general population. Their experiences, both during incarceration and post-release, offer critical insight into systemic obstacles affecting access to care. This study explores the perspectives of individuals who were pregnant while incarcerated in Ontario, Canada, examining their perinatal experiences and the factors contributing to adverse health outcomes for them and their newborns. Methods We undertook a qualitative study employing a descriptive design. We conducted virtual, semi-structured interviews with individuals who previously experienced incarceration while pregnant. Participants were recruited through purposeful and snowball sampling, and were eligible to participate if they had experienced incarceration in Ontario, Canada while pregnant. We conducted individual interviews to ensure confidentiality and encourage open discussions. We used thematic analysis to guide our identification and development of themes and subthemes. Results Eight participants were interviewed. Precarious perinatal care was identified as an overarching theme, encapsulating the instability and systemic challenges of perinatal care in carceral settings. Five main themes were identified: Carceral constraints to health and social supports, Mistreatment, Crystallization of pregnancy, (Im)personal care of pregnancy, and Parenting from the inside out. Participants described how power dynamics within carceral facilities affected access to perinatal care, expressed concerns about their own and their child’s health, and shared fears about reintegration post-release. Conclusion Participants described their perinatal experiences during incarceration, providing insight into the systemic and multifaceted barriers they encountered. This study enhances understanding of the complexities surrounding perinatal care access, illustrating how administrative processes and power dynamics within carceral facilities limit timely and appropriate care. These findings can inform the development of policies, procedures, and transitional resources during incarceration and post-release. Such interventions may improve perinatal experiences and contribute to better health outcomes for incarcerated pregnant individuals and their infants. Future research should explore perinatal care from the perspective of correctional officers working with incarcerated pregnant individuals. Additionally, examining policies governing carceral health and social service provision would help inform evidence-based reforms and improve care delivery.